Tensile strain hardening behaviour of hybrid steel-polyethylene fibre reinforced cementitious composites - Ahmed, Shaikh; Maalej, M. (Elsevier, 2009)
Tensile strain hardening and multiple cracking behaviours of fibre reinforced cementitious composites containing different hybrid combinations of steel (ST) and polyethylene (PE) fibres are reported. Various hybrid combinations of ST and PE fibres of 12 mm length are studied. Different hybrid combinations of ST and PE fibres of 18 mm length are also studied here. The effects of addition of different types of sands of different contents on the strain hardening behaviour are also evaluated. PE fibres are found to improve the tensile strain capacity of hybrid fibre composites whereas ST fibres contributed on the improvement of ultimate tensile strength of hybrid fibre composites. By increasing the length of PE fibres by 1.5 times significant increase in tensile strain capacity as well as improvement in strain hardening and multiple cracking behaviour of hybrid fibre composites is observed. The addition of sand adversely affected the strain hardening and multiple cracking behaviour of hybrid fibre composites with reduction in tensile strain capacity.